Role of CaMKII in Ang-II-dependent small artery remodeling - Prasad, Anand M. (Vascul Pharmacol, 2016)
Angiotensin-II (Ang-II) is a well-established mediator of vascular remodeling. The multifunctional calcium-calmodulin-dependent kinase II (CaMKII) is activated by Ang-II and regulates Erk1/2 and Akt-dependent signaling in cultured smooth muscle cells in vitro. Its role in Ang-II-dependent vascular remodeling in vivo is far less defined. Using a model of transgenic CaMKII inhibition selectively in smooth muscle cells, we found that CaMKII inhibition exaggerated remodeling after chronic Ang-II treatment and agonist-dependent vasoconstriction in second-order mesenteric arteries. These findings were associated with increased mRNA and protein expression of smooth muscle structural proteins. As a potential mechanism, CaMKII reduced serum response factor-dependent transcriptional activity. In summary, our findings identify CaMKII as an important regulator of smooth muscle function in Ang-II hypertension in vivo.